Epidemiology of pelvic and acetabular fractures in a tertiary hospital in Singapore - Amritpal Singh; Amaris Shu Min Lim; Bernard Puang Huh Lau; Gavin O’Neill (Singapore Medical Journal)
Introduction: Pelvic and acetabular fractures (PAFs) usually result from high-energy, potentially life-threatening accidents. They are one of the major injuries that lead to death in patients involved in such accidents. We studied the recent epidemiology of these injuries in Singapore. Methods: This is a retrospective data analysis of all trauma patients who underwent surgery for PAFs from 2008 to 2016 in a tertiary trauma centre in Singapore. Data including patient demographics, mechanism of injury and associated injuries was collected. Results: A total of 169 patients were admitted for PAFs over the eight-year period. The majority (79.3%) were male. The mean age was 41 (range 13–79) years. Most patients (51.5%) were Chinese. The most common mechanisms of injury were road traffic accidents (53.8%), falls (33.1%) and crush injuries (13.0%). 46.2% sustained acetabular fractures, while 44.4% sustained pelvic fractures. PAFs were most commonly associated with upper and lower limb injuries, followed by spinal and thoracic injuries. Average of length of stay in hospital was 24 (range 2–375) days. Conclusion: PAF predominantly affects young working males. Compared to previously published local data, there has been a significant reduction in the incidence of PAFs, likely due to improved road and work safety. The demographics of PAFs have changed, with fewer injuries in females (20.7% vs. 33.3%), a reduction in the proportion of injuries in the Chinese (51.5% vs. 70.1%). While road traffic accidents remain the most common cause, crush injuries are now more prevalent (13.0%).